THE EFFECTIVENESS OF CONTEXTUAL TEACHING AND LEARNING (CTL) IN EDUCATION: A SYSTEMATIC LITERATURE REVIEW AND META-ANALYSIS - Basuki; Sholeh Hidayat; Cecep Anwar Hadi Firdos Santosa (ZILLZELL MEDIA PRIMA, 2025)
The Contextual Teaching and Learning (CTL) approach emphasizes the interconnectedness between academic knowledge and real-life contexts so that learners can build meaningful understanding through authentic experiences. Although many studies on CTL were conducted in Indonesia, the results are still scattered and have not been comprehensively synthesized. Therefore, this study aims to conduct a Systematic Literature Review and meta-analysis to assess the effectiveness of CTL in improving student learning, motivation, communication, and collaboration outcomes in Indonesia. This study uses the Systematic Literature Review (SLR) approach with reference to the PRISMA 2020 guidelines. Articles published between 2013–2025 were searched from Google Scholar, Garuda, Scopus, and DOAJ databases using the keywords